2007
DOI: 10.1080/10640260701323490
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons between African American Girls' and Parents' Perceptions of Girls' Weight Concerns and Weight Control Behaviors∗

Abstract: Weight concerns and weight control behaviors were evaluated among sixty 8-10 year-old African American girls and their parents/caregivers. Girls completed the McKnight Risk Factor Survey and parents completed a modified version regarding perceptions of their daughters' concerns and behaviors. Significant correlations between girls' and parents' were seen for Overconcern with Weight and Shape (r = .56) and Weight Control Behaviors (r = .33). Parents' correctly identified 72% of girls' responses for Overconcern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Although prior research has found that African American girls are less concerned with weight, dieting behaviors, or being thin compared with their European American counterparts (Dalton et al, 2007;Dounchis et al, 2001;Logio, 2003;Lynch et al, 2004;Pernick et al, 2006;S. H. Thompson, Corwin, & Sargent, 1997), some researchers have suggested that this trend may soon be changing in this population.…”
Section: Acculturationmentioning
confidence: 96%
“…Although prior research has found that African American girls are less concerned with weight, dieting behaviors, or being thin compared with their European American counterparts (Dalton et al, 2007;Dounchis et al, 2001;Logio, 2003;Lynch et al, 2004;Pernick et al, 2006;S. H. Thompson, Corwin, & Sargent, 1997), some researchers have suggested that this trend may soon be changing in this population.…”
Section: Acculturationmentioning
confidence: 96%